BASIC RESEARCHSDF1/CXCR4 signalling promotes mobility of myeloma cells by activation and redistribution of cell surface adhesion molecules - Jinxiang, Fu; Xiaohui, Zhang; Yong, Zhang; Jianhua, Zhang; Ping, Chen; Jun, Li; Yu, Sun (Archives of Medical Science, 2009)
Introduction: The aim of the study was to investigate the effects of SDF-1a on multiple myeloma (MM) cell migration, adhesion and their corresponding signalling pathways. Material and methods: We studied the relationship between expression and distribution of the surface adhesion molecules and the ability of MM cells to migrate or adhere to stromal cells with or without SDF-1a in vitro . The effects of activation of phosphatidylinositol 3-kinase (PI3 kinase) in migration of MM cells was also investigated. Results: Flow cytometry analysis showed that MM cells expressed adhesion molecules such as CD29, CD44, CD49d and CD49e. Our results indicated that the SDF-1/CXCR-4 signalling promotes MM cells to adhere to marrow stromal cells in vitro . The migration of MM cells to stromal cells was enhanced in the presence of SDF-1a in a dose-dependent manner, which was inhibited by either pre-incubation of the MM cells with the G protein inhibitor PTX or the PI3 kinase inhibitor wortmannin. Polarization of adhesion molecules was a marked characteristic observed by confocal laser scanning microscopy (CLSM), which might contribute to the cells’ migration and adhesion to stromal cells. Meanwhile, we demonstrated that PI3 kinase played a role in the signalling pathway leading to Gia activation triggered by CXCL12 in MM cells. The effects of SDF-1/CXCR-4 signalling in MM cells’ polarization and motility might be mediated by Gia, which was required to activate PI3 kinase. Conclusions: Taken together, it is highlighted that SDF-1/CXCR4 is a critical regulator of MM migration, providing the framework for the inhibitors of this pathway to be used in future clinical trials to abrogate MM trafficking.